2020
DOI: 10.1080/07391102.2020.1802346
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of widely used and well-tolerated drugs as potential SARS-CoV-2 3C-like protease and viral RNA-dependent RNA polymerase inhibitors for direct use in clinical trials

Abstract: Despite strict measures taken by many countries, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to be an issue of global concern. Currently, there are no clinically proven pharmacotherapies for coronavirus disease 2019, despite promising initial results obtained from drugs such as azithromycin and hydroxychloroquine. Therefore, the repurposing of clinically approved drugs for use against SARS-CoV-2 has become a viable strategy. Here, we searched for drugs that target SARS-CoV-2 3C-like … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 89 publications
1
29
1
Order By: Relevance
“…Eltrombopag, an FDA approved drug used to treat low blood platelet count showed strongest binding affinity to PLpro enzyme suggesting potential inhibitor of the enzyme. Similar to the present finding, Gul et al (2020) also reported strong binding affinity of eltrombopag with 3CLpro and RdRp enzyme. Like many other studies, we also found strong binding affinity of ivermectin, an antihelmintic drug, with both the protease enzymes of SARS-CoV and -CoV-2.…”
Section: Lowsupporting
confidence: 92%
“…Eltrombopag, an FDA approved drug used to treat low blood platelet count showed strongest binding affinity to PLpro enzyme suggesting potential inhibitor of the enzyme. Similar to the present finding, Gul et al (2020) also reported strong binding affinity of eltrombopag with 3CLpro and RdRp enzyme. Like many other studies, we also found strong binding affinity of ivermectin, an antihelmintic drug, with both the protease enzymes of SARS-CoV and -CoV-2.…”
Section: Lowsupporting
confidence: 92%
“…This screening confirms previous reports demonstrating anti-SARS-CoV-2 activity of hydroxychloroquine, amlodipine besylate, arbidol hydrochloride, tilorone 2HCl, dronedarone hydrochloride, mefloquine, celecoxib, and thioridazine hydrochloride (8)(9)(10)(25)(26)(27), while identifying additional 12 drugs. However, there are seven drugs have been reported when our manuscript was underreview (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The underlying mechanisms of viral replication inhibition by these drugs are not clear.…”
Section: Discussionmentioning
confidence: 96%
“…29 In addition, severe acute respiratory syndrome-related coronavirus (SARS-CoV) encompasses a papain-like protease that significantly triggers an early growth response protein 1 (Egr-1)-dependent activation of transforming growth factor beta 1 (TGF-β 1), resulting in up-regulation of pro-fibrotic responses in vitro and in vivo in the lungs. [30][31] Recent computational methods study identified doxycycline among the drugs that could potentially be used to inhibit SARS-CoV-2 papain-like protease. 30,31…”
Section: Anti-inflammatory Effects Of Doxycyclinementioning
confidence: 99%
“…[30][31] Recent computational methods study identified doxycycline among the drugs that could potentially be used to inhibit SARS-CoV-2 papain-like protease. 30,31…”
Section: Anti-inflammatory Effects Of Doxycyclinementioning
confidence: 99%